Rainmaker Labs: Commercialising a great idea - NARASIMHALU, Arcot Desai (Institutional Knowledge at Singapore Management University, 2014)
In September 2013, Alex Leong, co-founder of Rainmaker Labs, considers where to invest the limited resources available to his technology start-up company in order to grow the business. Earlier that year, Rainmaker Labs launched ShopGuru, a mobile shopping application that enables users to earn and redeem loyalty points for browsing or shopping at select retail outlets. The ShopGuru application works hand-in-hand with Rainmaker’s proprietary iSenze hardware, which sends signals to the ShopGuru mobile application and captures information about each customer using the application. Keenly aware of the valuable customer data the company is collecting, Leong wants to further explore how this could be converted into a revenue opportunity. However, it has been a challenge to find investors, and after two and half years the company is still cash negative and operating on slim margins. Leong faces a common tech start-up dilemma — whether to focus their limited resources on expanding the business, or to strengthen their back-end systems and develop a stronger technology base to position future business growth. The flip side of this argument is equally relevant — good technology is only as good as its commercial application. This case also discusses the role of strategic business planning in commercialising a cutting-edge technology. Students will gain an understanding of developing a strategic business plan, growth strategies for start-ups, how to identify the ‘right’ partner, and outline the key characteristics of an entrepreneur. The case is suitable for undergraduate business management classes.